Capital Flows and Demographics-An Asian Perspective - Lueth, Erik. (Washington, D.C. : International Monetary Fund, 2008)
This paper calibrates the production functions of 176 countries to fit 2003 data and examines the capital flows that emerge, when labor forces change according to the 2007 UN population projections. It finds that demographic factors are no help in correcting today's global imbalances; that Japan's capital outflows have as much to do with population aging as with the yen carry-trade; and that China is key to understanding Asia's demographic impact on the world. It also finds that Asia offers the greatest arbitrage opportunities worldwide during the demographic transition and has the greatest potential for regional financial integration among world regions. Moreover, the demographic transition is unlikely to result in an asset price meltdown and could even raise world interest rates under perfect capital mobility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet